A systematic study of multi-layer graphene formation from hydrocarbon explosions: insights on temperature effects, syngas, and nitrogen-doping - Sigdel, Shusil (Kansas State University, 2023)
A systematic study on the formation and characterization of carbon formed during the explosion of various hydrocarbon precursors is presented. The carbon formed was a powder at higher precursor oxygen content and an aerosol gel at lower oxygen where the carbon yield was larger. The carbon formed linearly decreased with the O/C ratio, with some residual carbon at O/C greater than 1. The explosion temperature was measured by a spectrometer that detected black body, Planck radiation from the incandescent carbon, the analysis of which indicated temperatures in the range 1900–3100 K. The peak explosion temperature was found to increase with the oxygen-carbon (O/C) ratio. These findings were supported to some extent by theoretical calculations of the adiabatic flame temperature at constant volume based on the anticipated chemical reactions occurring during the explosion. The carbon collected was characterized by Raman, X-ray diffraction (XRD), high-resolution transmission electron microscopy (HRTEM), etc. HRTEM and Raman analyses indicated the presence of a threshold temperature of around 2100 K that separated two product types for all hydrocarbons: amorphous soot at temperatures less than 2100 K and multi-layer graphene at temperatures greater than 2100 K. The resulting graphene exhibited a turbostratic structure. The layers are stacked more randomly or misaligned, leading to a less structured and more disordered configuration, consisting of 6–30 layers depending on the O/C ratio and precursor used. Additionally, the explosion process yielded syngas as a byproduct gas for all hydrocarbons, with methane–producing only syngas. Nitrogen-doped graphene was produced using the explosion process using pyridine (C₅H₅N) as a precursor and introducing nitrogen-bearing gas during the explosion of acetylene and ethylene. X-ray photoelectron spectroscopy (XPS) analysis of the resulting carbon confirmed the presence of nitrogen, with the atomic percentage ranging from 0.6% to 3.4%, depending on the precursor material. Fine powder dispersion was conducted in 4 L and 17 L transparent plastic chambers using various powder dispersers. This dispersion system was then implemented in a 17 L aluminum chamber equipped with an ignition system to investigate the explosion of different powder samples. The experiments revealed incomplete combustion with longer burn times, and no graphene was produced.
Keywords: Oxygen-to-carbon; Explosion synthesis; Multi-layer graphene; Turbostratic graphene; Detonation graphene; High temperature